Acute suppurative thyroiditis seeded from infective endocarditis and intravenous drug use. (2021) - Cheung, Brian; Levy, Chris; Cheung, Michelle; Dhanaraja, Amirtharaj; Abraham, Renny; Duvoor, Chitharanjan
Highlights: AST is a rare infection of the thyroid gland and usually requires empiric antimicrobial therapy. Patients with AST can present with euthyroidism, hypothyroidism, or hyperthyroidism. Antithyroid drugs are not indicated in patients with AST. Abstract: Acute suppurative thyroiditis (AST) is a rare infection of the thyroid gland, and most patients are euthyroid upon presentation. We present an interesting case of a 42-year-old man with a history of intravenous drug use (IVDU) and poorly controlled type 2 diabetes mellitus who was admitted for sepsis and thyrotoxicosis from infective endocarditis (IE), AST, prostate abscess, and pyelonephritis. He suffered from a cerebral vascular accident (CVA) from septic embolic showering. Thyroid-stimulating hormone (TSH) was <0.10 mIU/L, and free thyroxine (T4) levels were>90 pmol/L. Methicillin-resistant Staphylococcus aureus (MRSA) was cultured in the patient's blood and urine. He was treated with prompt intravenous (IV) antimicrobials and source control from a transurethral resection of the prostate. This case demonstrates that AST can be a potential complication of IE and IVDU.